Modeling the Effectiveness of Intelligent Systems in Public Transport That Uses Low-Carbon Energy: A Case Study - Justyna Patalas-Maliszewska; Hanna Łosyk; Jacek Newelski (Energies, 2021)
Cities have been struggling for many years with many transport problems, including the impact of carbon monoxide emitted by vehicles on the environment, traffic jams, high energy consumption, numerous accidents or high infrastructure costs. There is also a dynamic growth of vehicles on the roads, which is why an increasing number of cities are introducing intelligent transportation systems (ITS), which is part of the concept of smart cities. This paper proposes a new matrix to assess the effects of the ITS implementation in the context of a concept Smart City, which consists of five criteria: (1) movement speed; (2) safety; (3) environmental; (4) economic; (5) satisfaction and amenities for society/passengers. In this new approach the benchmark values of the indicators assigned to the criteria are involved and, therefore, it is possible to determine the level of effectiveness of the ITS in public transport that uses low-carbon energy. This research used literature studies to establish the criteria of effectiveness of ITS as well as a case study, namely public transport that uses low-carbon energy in a Polish city, which had the largest fleet of electric buses in Poland and implements and uses an ITS. Both, the theoretical and the empirical research results demonstrate the usefulness and potency of the proposed matrix to assess the effects of the ITS implementation in cities in the context of the development of a smart city. In that way, the proposed approach may be a useful tool for measuring the effects of ITS implementation in cities.